Influence of 16S rRNA Hypervariable Region on Estimates of Bacterial Diversity and Community Composition in Seawater and Marine Sediment - Kerrigan, Zak; Kirkpatrick, John B.; D’Hondt, Steven (Frontiers in Microbiology, 2019)
To assess the influence of 16S rRNA tag choice on estimates of microbial diversity and/or community composition in seawater and marine sediment, we examined bacterial diversity and community composition from a site in the Central North Atlantic and a site in the Equatorial Pacific. For each site, we analyzed samples from four zones in the water column, a seafloor sediment sample, and two subseafloor sediment horizons (with stratigraphic ages of 1.5 Ma and 5.5 Ma). We amplified both the V4 and V6 hypervariable regions of the 16S ribosomal RNA gene (rRNA) and clustered the sequences into operational taxonomic units (OTUs) of 97% similarity to analyze for diversity and community composition. OTU richness is much higher with the V6 tag than with the V4 tag, and subsequently OTU-level community composition is quite different between the two tags. Vertical patterns of relative diversity are broadly the same for both tags, with maximum taxonomic richness in seafloor sediment and lowest richness in subseafloor sediment at both geographic locations. At the class level, community composition is very similar for both tags. For each tag, class-level diversity and community composition of water-column samples are very similar between the Atlantic and Pacific. However, also for each tag, sediment communities differ greatly from the Atlantic to Pacific. Finally, for relative patterns of diversity and class-level community composition, deep sequencing and shallow sequencing provide similar results.